2021
DOI: 10.1016/j.jse.2020.11.022
|View full text |Cite
|
Sign up to set email alerts
|

A single dose of tranexamic acid reduces blood loss after reverse and anatomic shoulder arthroplasty: a randomized controlled trial

Abstract: Background: Hematoma formation and the need for blood transfusions are commonly reported complications after shoulder arthroplasty. Tranexamic acid (TXA) has been widely used in hip and knee arthroplasty to decrease perioperative blood loss. The role of TXA is still being established in shoulder arthroplasty. Materials and methods: We conducted a double-blind randomized controlled trial comparing intravenous TXA vs. placebo in 60 patients undergoing primary anatomic or reverse shoulder arthroplasty. Of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…13 Cunningham et al reported a mean BMI of 30±7.0 kg/m2 for TXA group,and 31±7.8 kg/m 2 for the non-TXA group. 12 There were no significant differences between the two groups in any of the four studies.…”
Section: Study Characteristicsmentioning
confidence: 78%
See 4 more Smart Citations
“…13 Cunningham et al reported a mean BMI of 30±7.0 kg/m2 for TXA group,and 31±7.8 kg/m 2 for the non-TXA group. 12 There were no significant differences between the two groups in any of the four studies.…”
Section: Study Characteristicsmentioning
confidence: 78%
“…As a new RCT study reported a single dose of tranexamic acid in shoulder arthroplasty, a meta-analysis needs to performed. 12 This systematic review and meta-analysis aimed to evaluate extant Level I randomized controlled trials (RCTs) examining the efficacy of TXA in primary shoulder arthroplasty.…”
Section: Level Of Evidence: Level ⅰ Systematic Review and Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations